2021
DOI: 10.1002/gps.5581
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of randomised controlled trials of physical activity in people with Alzheimer's disease and mild cognitive impairment with a comparison to donepezil

Abstract: Objectives Physical exercise may benefit people with Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, randomised controlled trials (RCTs) of exercise have shown conflicting findings and it is unclear if positive outcomes are comparable to a commonly used cholinesterase inhibitor, donepezil. Methods Embase, Medline, PsycINFO, PsycARTICLES, SCOPUS were searched for RCTs of physical activity compared to a control condition, and donepezil compared to placebo in people with AD and MCI. Effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Although many meta-analyses have indicated the effects of exercise on adults with AD [17,27,53], there are differences in selection criteria between our study and previous studies. Due to the different mechanisms of dementia, abnormal protein deposits may coexist with neuro-vasculature at different stages of dementia and influence brain function [54].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although many meta-analyses have indicated the effects of exercise on adults with AD [17,27,53], there are differences in selection criteria between our study and previous studies. Due to the different mechanisms of dementia, abnormal protein deposits may coexist with neuro-vasculature at different stages of dementia and influence brain function [54].…”
Section: Discussionmentioning
confidence: 93%
“…Although many systematic review studies have examined the effects of exercise on cognition and physical performance in adults with AD, they have commonly shown inconclusive results due to inconsistent inclusion criteria, considerable heterogeneity (I 2 ≈ 80%) across studies, a small number of included studies, and different types of dementia populations (e.g., Lewy body dementia and vascular dementia) [16,17,27]. They have considered the limitations of previous studies and the fact that a growing body of new RCT studies published in Chinese and English language is investigating the effect of exercise on cognition and ADL in populations with AD.…”
Section: Introductionmentioning
confidence: 99%
“…In THY-Tau22 mice, long-term voluntary wheel running for 9 months reversed pathological reduction of ChAT + neurons in the MS-DB; this was accompanied by improvements in tau pathology and neuroinflammation within the hippocampus ( Belarbi et al, 2011 ). Moreover, where comparisons were possible, the effect size for exercise was generally comparable with that of donepezil ( Pisani et al, 2021 ). In Aβ 25–35 -induced rats, both chronic aerobic and resistance exercise have similar effects to those of AChEIs, reducing AChE activity and reversing recognition memory deficits ( Farzi et al, 2019 ).…”
Section: Cholinergic Systemmentioning
confidence: 87%
“…As the most common cause of dementia, Alzheimer’s disease is characterized by progressive and irreversible cognitive and memory loss, affecting an increasing population of the elderly worldwide ( Pisani, Mueller, 2021 ). Remarkably, recent studies have shown that people with mild cognitive impairment, although is normal in aging, have a three to five times higher risk of developing dementia, especially Alzheimer’s disease ( Bennett, Wilson, 2002 ).…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 99%